Management and Certification Process for Organic Production in Ukraine and Poland - Ruslan Buriak; Victor Artish; Mykola Orlykovskyi (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
A systematic analysis of trends in the development of organic products in Ukraine and Poland was carried out, which showed that the total area of certified ecological lands for the study period from 2006-2016 in Ukraine increased by 1.7 times, and in Poland from 2004-2014 it increased by 12 times. It has been established that the most significant impact on qualitative structural changes in the economic sector is adjustment to European standards that establish a favorable system of agricultural production regulation, marking and inspection of organic products. This is why Poland, while being in the European Union, has a significant advantage over Ukraine. The system of control and certification by the authorized bodies is generalized, as well as the mechanism of financial support for organic agricultural production. The necessity of using the experience of Poland with the purpose of greening agriculture and development of organic agricultural production in Ukraine is emphasized.